EKSISTENSI MAHASISWA KAMPUS MENGAJAR ANGKATAN 5 DALAM MENINGKATKATKAN KETERAMPILAN LITERASI DAN NUMERASI SEKOLAH DASAR - Restu Januarty Hamid; Nurfaizah Sahib; Aljuwanti (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Literacy and numeracy are fundamental skills that academic staff members need to analyze any text or image in a variety of contexts. It is understandable that both literacy and student enrollment rates in Indonesia are very low. The Ministry of Education and Culture as a result introduced a program called Teaching Campus through the Merdeka Learning Kampus Merdeka (MBKM) initiative. This program motivates students to contribute in improving the education of students who are literate and numerate, Elementary Schools. Students continue to work tirelessly to support schools, teachers and students based on current circumstances and needs. Expanding literacy and numeracy education can connect more effectively. As a result, numeracy literacy instruction is very important to improve reading and arithmetic learning in elementary schools, as has been done at the Teaching Campus Batch 5. Carrying out literacy using letter cards, implementing the Quizizz application, and implementing numeracy using smart ladder media, numeration trees, and crossword puzzles can improve skills. Focusing on literacy and numeracy guidance activities, student use of technology, emotional intelligence, and the ability to create cool class characters for students. Keywords: Literation, Numeration, Freedom of Learning Independent Campus